The Implementation of Read, Encode, Annotate, Ponder (REAP) Strategy in Teaching Students’ Reading - Elina Lulu B. Rumapea; Tiodora Silalahi; Tumpal Siahaan (Budapest International Research and Critics University, 2022)
In this research, the data was analyzed from quantitative data. The quantitative data was taken from the mean of students score in taking test in form written test. This research was conducted in two classes which consist of 56 students. The class named VII-A and VII-B of SMP Swasta Teladan Pematangsiantar In order to find out the improving the students’ reading ability, the writer created a pre-test about describe someone. Then, the writer taught the students by using REAP strategy. After that, the created a post test about also described. The writer decided the score of both pre test and post-test by using REAP Strategy. The analysis of the data are started from scoring the students reading ability of the Explanation text, tabulating the pre test and post test student’s score, then calculating the coeficient correlation by using SPSS. The writer found the result of research as follows the score of Reading Ability test of Explanation text from 28 students is low where the total of pre test score is 1280.